Determination Of Total Alkaloid Content Of Yellow Wood (Arcangelisia flava (L.) Merr) Extract Based On Differences In Ethanol Concentration Using Uv-Vis Spectrophotometry Method - Yuliana, Rika; Daulay, Anny Sartika; Ridwanto, Ridwanto; Rahman, Fathur (Indonesian Journal of Science and Pharmacy, 2023)
Yellow wood with its secondary metabolites is one of the plants that has the potential as a traditional medicinal plant to treat various diseases, such as cancer. The chemical compounds contained in yellow wood are alkaloids, saponins, tannins, flavonoids, steroids/triterpenoids. The objective of this research was to determine the chemical compounds contained in ethanol extract and determine the total alkaloid value of yellow wood extract. This research method is an experimental method which includes processing plant materials, making ethanol extract concentrations of 50, 70 and 96%. Characterization examination, phytochemical screening and determination of total alkaloid levels of yellow wood extract by Uv-Vis spectrophotometry method. The results of phytochemical screening on yellow wood ethanol extract contain chemical compounds such as alkaloids, saponins, tannins, flavonoids, steroids/triterpenoids. Determination of total alkaloid levels is carried out by determining the maximum wavelength of caffeine, measuring the kaffein calibration curve and calculating total alkaloid levels using the Uv-Vis spectrophotometry method. Results The determination of total alkaloid levels in ethanol solvent extract concentration of 50% is 2.9649 ± 0.1767%, ethanol solvent extract with a concentration of 70% is 6.0180 ± 0.2469% and ethanol solvent extract with a concentration of 96% is 10.92001 ± 2.7803%.